ONBOARDING IN RECRUITMENT OF THE MODERN WORKPLACE: A LITERATURE REVIEW - Maharani, Apriana Dewi; Izzati, Umi Anugerah; Ramadhan, Reza Dwi (Bina Bangsa International Journal of Business and Management, 2025)
This research investigates the strategic role of onboarding as part of modern recruitment and employee integration practices. Utilizing a Systematic Literature Review (SLR) approach, the research examines between 50 and 15 peer-reviewed publications selected and released between 2020 and 2025 in order to pinpoint innovations, advantages, and alignment with current HR trends about onboarding. As described in most of the analyzed research, the results confirm a five-stage theoretical framework of onboarding, preboarding, orientation, integration, execution, and delivering results. Furthermore, the study backs up the growing idea that onboarding is a strategy for human resources as well as a tool for sustainability and digital transformation, especially when it comes to the usage of remote onboarding technologies and paperless systems. Quantitatively, the results show that 86.7% (13 of 15) of the journals directly address onboarding in the context of the modern work environment. Improved role clarity, early-stage confidence, social integration, a quicker time to productivity, and support for Green HRM are among the fundamental advantages that are highlighted across the literature. The study solely looks at onboarding in the early phases of recruitment and is restricted for new hires than about employee’s long-term retention. Future studies could investigate empirical findings from surveys or interviews, look at onboarding procedures in certain sectors, and assess how they affect long-term results like job satisfaction and retention. All things considered, onboarding is a game- changing procedure for creating inclusive and long-lasting workforces.